Depression, Anxiety, Resilience and Coping Pre and Post Kidney Transplantation - Initial Findings from the Psychiatric Impairments in Kidney Transplantation (PI-KT)-Study - Mueller, Helge H.; Englbrecht, Matthias; Wiesener, Michael; Titze, Stephanie; Heller, Katharina; Groemer, Teja W.; Schett, Georg; Eckardt, Kai-Uwe; Kornhuber, Johannes; Maler, Juan Manuel (PLoS ONE, 2015)
Depression/anxiety, impaired Health-Related Quality of Life (HRQoL) and coping and resilience structures, are associated with increased mortality/poor outcome in chronic kidney disease (CKD) patients before (CKD/pre-KT) and after kidney (CKD-T) transplantation. Less is known about prevalence rates of psychiatric symptoms and impaired HRQoL of non-transplanted compared with transplanted patients.In a cross-sectional study comparing 101 CKD/pre-KT patients with 151 cadaveric-transplanted (CKD-T) patients, we examined prevalence of depression/anxiety (HADS questionnaire) and coping, resilience and HRQoL (SF-12, Resilience-Scale and FKV-questionnaire).The prevalence of both depressive and anxiety symptoms was not significantly different between different pre-/and CKD-T patient groups. In CKD-T no significant relations of coping strategies with kidney function were identified. Furthermore, the Resilience Scales for acceptance and competence did not suggest any differences between the CKD/pre-KT and CKD-T subgroup. In the CKD/pre-KT patients, significant correlations were identified between the acceptance subscale and partnership, as well as between the competence subscale and older age/partnership.Both the CKD/pre-KT and CKD-T patients exhibited notable impairments in the HRQoL which which showed a comparable pattern of results. KT itself does not appear to be the main risk factor for the development of mental impairments.
EVALuna2:3811